2011
DOI: 10.1111/j.1601-183x.2011.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional dissection of Odorant binding protein genes in Drosophila melanogaster

Abstract: Most organisms rely on olfaction for survival and reproduction. The olfactory system of Drosophila melanogaster is one of the best characterized chemosensory systems and serves as a prototype for understanding insect olfaction. Olfaction in Drosophila is mediated by multigene families of odorant receptors and odorant binding proteins (OBPs). Although molecular response profiles of odorant receptors have been well documented, the contributions of OBPs to olfactory behavior remain largely unknown. Here, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
192
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(206 citation statements)
references
References 47 publications
14
192
0
Order By: Relevance
“…In our study, some OBPs showed the same response to MIX treatment and were highly expressed at all physiological stages. This result further supports the view that OBPs are not just simple, general solubilizers that act as transporters for odorants but also play a vital role in the perception of different kinds of chemicals in the environment (Pelosi et al, 2006;Swarup et al, 2011). An OBP in Hylamorpha elegans showed a high binding affinity to β-ionone (Venthur et al, 2016), a volatile compound derived from plant carotenoids (Simkin et al, 2004).…”
Section: Discussionsupporting
confidence: 77%
“…In our study, some OBPs showed the same response to MIX treatment and were highly expressed at all physiological stages. This result further supports the view that OBPs are not just simple, general solubilizers that act as transporters for odorants but also play a vital role in the perception of different kinds of chemicals in the environment (Pelosi et al, 2006;Swarup et al, 2011). An OBP in Hylamorpha elegans showed a high binding affinity to β-ionone (Venthur et al, 2016), a volatile compound derived from plant carotenoids (Simkin et al, 2004).…”
Section: Discussionsupporting
confidence: 77%
“…Some studies have demonstrated that reduced expression or genetic alteration of an OBP can lower the sensitivity of a sensory neuron to its odor ligand and/or alter chemosensory behavioral phenotypes (e.g. Syed et al, 2006;Pelletier et al, 2010;Wang et al, 2010;Swarup et al, 2011); other studies have demonstrated promising methodologies that reduce OBP expression but have not characterized resulting physiological or behavioral phenotypes (e.g. Sengul and Tu, 2010).…”
Section: Introduction Q3mentioning
confidence: 98%
“…The OBPs are believed to solubilize volatile hydrophobic molecules, enabling their delivery to odor receptors via the sensillum lymph (Sanchez-Gracia et al, 2009;Zhou, 2010;Swarup et al, 2011). The OBPs contain two or three disulfide bridges.…”
Section: Introductionmentioning
confidence: 99%